The Political Alienation of the Intellectual in Recent Zairian Fiction - Janice Spleth (Studies in 20th & 21st Century Literature, 1991)
A high proportion of recent Zairian fiction features intellectuals—educators, priests, students, and professionals—as major characters who are in some way alienated from society. This study documents the extent of this occurrence in novels by Mbwil a Mpang Ngal, V. Y. Mudimbe, Bolya Baenga, and Pius Ngandu Nkashama and, at the same time, relates the situation of the intellectual as seen in these works to some of the social and political factors peculiar to Zaire's colonial history and post-independence evolution. Analyses of individual novels provide the basis for a discussion of Belgian colonial policies regarding the évolué, the ambiguous role of the African priest in the Congo, the growing corruption of the new governing elite since independence, and the ongoing political repression of intellectuals who oppose the status quo. While the characters in the works under examination suffer from different sorts of alienation, all of them are in some way victims of changes in class structure during the post-colonial period.
Keywords: Zairian fiction; Zairian; educators; priests; students; professionals; Mbwil a Mpang Ngal; V. Y. Mudimbe; Bolya Baenga; Pius Ngandu Nkashama; social factors; political factors; Zaire' s colonial history; Zaire; post-independence evolution; individual novels; novel; Belgian colonial; évolué; ambiguous; role; African priest; Congo; corruption; independence; political; repression; alienation; victims of change; victims; class structure; post-colonial period; post-colonialism